Intrusion detection in computer systems - Gavrylenko, Svitlana; Chelak, Viktor Vladimirovich; Hornostal, Aleksey (Technical University of Sofia, 2016)
The work proposes to use the mathematical formalism of statistical analysis based on the BDS-test, Shewhart control cards and CUSUM to develop patterns of identification of the computer system in a state of computer viruses attacks.

В работе предлагается использовать математический аппарат статистического анализа на основе BDS-тестов, контрольных карт Шухарта, карт КУСУМ для разработки шаблонов идентификации состояния компьютерной системы в условиях воздействий компьютерных вирусов.
Обнаружение вторжений в компьютерные системы
Keywords: BDS-statistics; Shewhart control cards; CUSUM cards; security of computer systems; computer virus; BDS-статистика; контрольные карты Шухарта; карты КУСУМ; безопасность компьютерных систем; компьютерный вирус